If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + 12 = x + -4(6 + 2x) + 9x Reorder the terms: 2(-4 + x) + 12 = x + -4(6 + 2x) + 9x (-4 * 2 + x * 2) + 12 = x + -4(6 + 2x) + 9x (-8 + 2x) + 12 = x + -4(6 + 2x) + 9x Reorder the terms: -8 + 12 + 2x = x + -4(6 + 2x) + 9x Combine like terms: -8 + 12 = 4 4 + 2x = x + -4(6 + 2x) + 9x 4 + 2x = x + (6 * -4 + 2x * -4) + 9x 4 + 2x = x + (-24 + -8x) + 9x Reorder the terms: 4 + 2x = -24 + x + -8x + 9x Combine like terms: x + -8x = -7x 4 + 2x = -24 + -7x + 9x Combine like terms: -7x + 9x = 2x 4 + 2x = -24 + 2x Add '-2x' to each side of the equation. 4 + 2x + -2x = -24 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + 0 = -24 + 2x + -2x 4 = -24 + 2x + -2x Combine like terms: 2x + -2x = 0 4 = -24 + 0 4 = -24 Solving 4 = -24 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 12×-1/3 | | 13=10 | | 3log(2)x=28 | | -53/4-31/2= | | 4x-40=13-6x+3 | | 2y-10x=10 | | 3.50x=10.50 | | 3x^2+10=100 | | 2x+7=15+4x | | 2x+12+9=x+3 | | 6x+5+9x-10+80+90=360 | | X+6=-8x+5 | | (x^2+0.8)(x^2+0.8)= | | 3x-29=17-5x | | 18=9+3h | | 7tanx+2=9 | | 3y+6-2=8-2y | | 7/3*8/6 | | -4/7y16 | | 12=15-3p | | 2(x-4)+12=x-4(6+2x)+9 | | 42r^2-35r=0 | | -5+1y=-8x | | 15=2v+3 | | 9p-4q=-15 | | 8=10-2r | | -6x+3=-6x-5 | | 4x+7x-8=-19 | | 40=5e | | 3x^2+7=301 | | 5+2x=3x+-4 | | -x-29=37-4x |